Global Labour History: A State of the Art - Frank, David (Labour / Le Travail, 2008)
The article reviews the book, "Global Labour History: A State of the Art," edited by Jan Lucassen.
Keywords: BOOKS -- Reviews; GLOBAL Labour History: A State of the Art (Book); LUCASSEN, Jan; Labor; Nonfiction

Trinity of Passion: The Literary Left and the Antifascist Crusade - Frank, David (Labour / Le Travail, 2008)
The article reviews the book, "Trinity of Passion: The Literary Left and the Antifascist Crusade," by Alan M. Wald.
Keywords: ANTI-fascist movements; BOOKS -- Reviews; Nonfiction; TRINITY of Passion: The Literary Left & the Antifascist Crusade (Book); WALD, Alan M.

Theorizing Historical Consciousness - Frank, David (Labour / Le Travail, 2005)
The article reviews the book, "Theorizing Historical Consciousness," edited by Peter Seixas.

The Progressive Tradition in Canadian Literature - Frank, David (Labour / Le Travail, 2003)
The article reviews and comments on the book, "Progressive Heritage: The Evolution of a Politically Radical Literary Tradition in Canada," by James Doyle.
Keywords: BOOKS -- Reviews; Canadian literature; DOYLE, James; Nonfiction; PROGRESSIVE Heritage: The Evolution of a Politically Radical Literary Tradition in Canada (Book)

Colliers Across the Sea: A Comparative Study of Class Formation in Scotland and the American Midwest, 1830-1924 - Frank, David (Labour / Le Travail, 2001)
The article reviews the book, "Colliers Across the Sea: A Comparative Study of Class Formation in Scotland and the American Midwest, 1830-1924," by John H. M. Laslett.

Short Takes: The Canadian Worker on Film - Frank, David (Labour / Le Travail, 2000)
Is there a Canadian labour film? After a century of film production in Canada, the answer is uncertain. Canadian workers do appear in a variety of documentary and feature film productions, but their presence often arises from the incidental processes of documentation and fictionalization. There is also a more purposeful body of work focused on the concerns of labour history, but its promise remains relatively underdeveloped. Although film has become one of the dominant languages of communications at the end of the 20th century, the practice of visual history stands to benefit from closer collaboration between historians and filmmakers.

The Struggle Against Wage Controls: The Saint John Story, 1975-1976 - Vair, George; Canadian Committee on Labour History (Past CCLH Publications, 2006)
In October 1976 one million Canadian workers walked off the job to protest the wage controls imposed by Prime Minister Pierre Elliott Trudeau. In a memorable personal account of this historic general strike, Saint John labour activist George Vair recalls how workers in one New Brunswick city mobilized to defend themselves and their unions and defeat the unpopular program. --Publisher's description
Keywords: General Strike, Saint John, N.B., 1976; Government policy; History; Labor movement; Strikes and lockouts; Wages

Working-Class History - Rouillard, Jacques; Frank, David; McCallum, Todd; Palmer, Bryan D. (The Canadian Encyclopedia (TCE), 2006)
Working-class history is the story of the changing conditions and actions of all working people. Most adult Canadians today earn their living in the form of wages and salaries and thus share the conditions of dependent employment associated with the definition of "working class." -- Introduction